Terracentrism and Spradleys’s Domain Analysis: A Study on the Deprivation of Indonesian Long-Term Local Wisdom on Maritime Life - Kurniawan, Iwan; Wijanarko, R.Benny (UM Purwokerto Press, 2024)
This study examines the impact of terracentrism on the deprivation of Indonesian long-term local wisdom on maritime life. Terracentrism, a phenomenon where land-based perspectives dominate over sea-based ones, has led to the erosion of traditional maritime knowledge and practices in Indonesia. The research employs domain analysis, a qualitative methodology inspired by Spradley's approach, to investigate the experiences and perceptions of local communities affected by this deprivation. The findings reveal that terracentrism has resulted in the loss of essential skills and knowledge necessary for sustainable maritime livelihoods. The study highlights the significant impact of this deprivation on the social, economic, and environmental well-being of coastal communities. Furthermore, it underscores the importance of preserving and promoting local wisdom in the face of globalization and environmental changes. The implications of this study emphasize the need for policymakers and stakeholders to recognize the value of traditional maritime knowledge and to incorporate it into modern conservation and management strategies. By doing so, they can help mitigate the negative effects of terracentrism and ensure the long- term sustainability of Indonesia's maritime life.